High‐Rate Fluid Injection Reduces the Nucleation Length of Laboratory Earthquakes on Critically Stressed Faults in Granite. Issue 23 (9th December 2022) - Ji, Yinlin; Wang, Lei; Hofmann, Hannes; Kwiatek, Grzegorz; Dresen, Georg
Abstract: We conducted fluid injection experiments on cylindrical low‐permeability granite samples with a critically stressed sawcut fault at local injection rates of 0.2 and 0.8 mL/min and confining pressures of 31 and 61 MPa. A local array of six strain gauges attached close to the faults allows us to estimate the nucleation length of each injection‐induced dynamic slip event (i.e., laboratory earthquake). We find nucleation lengths decrease from approximately 90% to <15% of the fault length with higher injection rate and increased effective normal stress. Injection‐induced laboratory earthquakes with smaller nucleation lengths show generally higher peak slip rates and larger fault slip displacements, signifying an intensified seismic hazard. Our results also indicate that initially stable fault patches may be reactivated to slip seismically by increasing injection rates. This study systematically demonstrates that higher injection rates constitute dynamic loading, which increase the seismic hazard by shrinking the earthquake nucleation length. Plain Language Summary: Earthquakes associated with fluid injection in various geo‐energy settings, such as shale gas and deep geothermal energy, have shelved many projects with great potential. However, the injection‐rate dependence of earthquake nucleation length, which characterizes the length of a slowly slipping (creeping) fault patch in preparation for a subsequent earthquake, remains to be studied. To this end, we performed fluid injection experiments on low‐permeability granite samples containing a critically stressed sawcut fault. We demonstrate that the nucleation length of injection‐induced laboratory earthquakes shrinks with higher effective normal stress and larger injection rate. We show that laboratory earthquakes induced by higher fluid injection rates are characterized by smaller nucleation lengths, faster peak slip rates, and larger fault slip displacements. Our results also suggest that a stable fault patch subject to low‐rate injection may be induced to slip seismically by increasing injection rates. Our findings may explain the higher seismic hazards associated with higher injection rates as has been frequently documented in field cases. Key Points: The nucleation length of injection‐induced laboratory earthquakes reduces with higher injection rate and greater effective normal stress Injection‐induced laboratory earthquakes with smaller nucleation lengths exhibit higher peak slip rates and larger fault slip displacements Fast‐rate fluid injection may cause initially stable fault patches of smaller sizes to slip seismically, leading to higher seismic hazards